ESCHERICHIA COLI IN THE RECTAL SWAB OF KOI FISH MAINTAINED IN ISOLATION PONDS DURING QUARANTINE PERIOD - Widiarta, Kadek Apriyan; Mahatmi, Hapsari; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana, 2022)
Koi fish (Cyprinus carpio) is one of the freshwater ornamental fish commodities which has a very high economic value and is of high interest. Koi fish are generally transported by land. This condition can cause koi to become stressed, which has an impact on decreasing health and even disease errors. One indicator of koi health problems can be seen from the presence of E. coli. This study aims to see the Escherichia coli bacteria in koi fish kept in isolation ponds during the quarantine period using 19 samples of isolates from rectal swabs which were then taken to BBVET Denpasar for isolation and identification of E. coli bacteria. This study used an exploratory observation design with a cross-sectional method, while the sample was taken by purposive sampling. The data obtained were descriptive qualitative. The result of this study are known from 19 samples that be examined  show five samples positive of Escherichia coli bacteria (26,3%) which is three samples (15,9%) came from Tulungagung koi and two samples (10,3%) came from Blitar koi.